Chronic Osteomyelitis of the Distal Femur Treated with Resection and Delayed Endoprosthetic Reconstruction: A Report of Three Cases. (15th August 2017) - Ryan, Sean; Eward, William; Brigman, Brian; Zura, Robert
Abstract : Chronic osteomyelitis involving the distal femur often results in amputation or arthrodesis. This article presents three cases of chronic osteomyelitis treated with a staged approach culminating in endoprosthetic reconstruction. Stage one involved resection of infected bone and placement of an intramedullary nail spanning the bony defect between proximal femur and tibia, with antibiotic cement packed around the nail. Patients were then placed on long-term IV +/− oral antibiotics to clear the infection. A "cooldown" period was then used between stages where patients were off antibiotics and inflammatory markers were monitored for signs of remaining infection. Stage two then involved reconstruction of the distal femur and knee with an endoprosthesis. In the appropriate patient, this treatment strategy offers another option in this challenging population.